Molecules and functions of aesculus chinensis bunge bark volatiles - Li, Zuming (Emirates Journal of Food and Agriculture, 2018)
This paper analyzes the organic solvent extracts of Aesculus chinensis Bunge Bark using TG and Py-GC-MS. The pyrolysis products were analyzed by GC-MS. The results showed that the extracts of Aesculus chinensis Bunge Bark contain a large number of biologically active components, including hydrocarbons, acids, ethers, alcohols, and phenols. The main components in the extract of Aesculus chinensis Bunge Bark are healthy and abundant; the main representatives of the active ingredients are Scopoletin Vanillin, Eugeno, Pyridine, p-Cresol, Indoles, Maltol and Furfural. There are potential applications in bioenergy, biopharmaceuticals, cosmetics, skin care products, and spices.